Global scientific trends on matrix metalloproteinase and osteosarcoma: A bibliometric and visualized analysis - Wu, Xin; Ma, Shiwei; Wu, Zhongguang; Zhao, Qiangqiang (Frontiers in Oncology, 2023)
Objective This study aimed to identify author, country, institutional, and journal collaborations and their impacts, assess the knowledge base, identify existing trends, and uncover emerging topics related to the role of Metalloproteinase in osteosarcoma. Methods 945 Articles and reviews associated with the role of Metalloproteinase in osteosarcoma were obtained from the WoSCC and analyzed by Citespace and Vosviewer. Results The main aspects of research on the role of MMP in OS are invasion and metastasis. The latest hotspots were found to be the mechanism of MMP promoting invasion and metastasis, lung metastasis, and antitumor activity. Notably, invasion, metastasis, and antitumor activity were potentially turning points in the MMP-OS field. In the future, the primary research hotspot in the field of MMP-OS may be to study the mechanism, explore their role in the OS lung metastasis, and determine their role in the cancer therapy process. Conclusion This study thus offers a comprehensive overview of the MMP-OS-related field using bibliometrics and visual methods, which will provide a valuable reference for researchers interested in the field of MMP-OS.